Examining the Relationships of Work Stress, Time Budget Pressure, and Obedience Pressure on the Performance of BPK RI Auditors in Bali Province - I Gusti Ayu Agung Adinda Prameswari Anom; Ni Luh Sari Widhiyani (E-Jurnal Akuntansi, 2025)
This study aims to examine the relationship between work stress, time budget pressure, and obedience pressure on auditor performance. The research was conducted at the BPK RI Representative Office in Bali Province. A purposive sampling method was employed, resulting in a sample of 95 respondents, all of whom were auditors at the BPK RI Bali Representative Office. Data were analyzed using Multiple Linear Regression Analysis with the SPSS software. The findings reveal that work stress, time budget pressure, and obedience pressure have a negative and significant impact on auditor performance. These results are consistent with the inverted U-curve theory, which suggests that performance decreases when stress levels exceed an optimal point. Based on these findings, it is recommended that the BPK RI Representative Office in Bali Province assigns tasks that align with the auditors' capabilities and provides sufficient time to complete audits, thereby minimizing the negative effects of excessive pressure.